Efektivitas Perjanjian Buyback Guarantee bagi Para Pihak Sebagai Akibat Wanprestasi oleh Debitur - Prima Riza Aulianur; Gunardi Lie (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
This paper aims to analyze and understand the position of the Developer towards the Bank as the provider of mortgage facilities in the implementation of buyback guarantee. Additionally, it is hoped that this paper can provide additional understanding and information for academics, especially in the field of property, and understand how the buyback arrangement applied by the Developer with the Bank. The research method used in this discussion is empirical juridical research by looking at articles that regulate the right to repurchase sold goods based on Article 1519 of the Civil Code using the Conceptual Approach and Statute Approach. The types and sources of law used include primary and secondary data by analyzing based on regulations applicable in Indonesia. The data collection techniques used are observation and interviews. The analysis technique used is qualitative analysis. From the agreements made by the parties, referring to Article 1338 of the Civil Code, the Cooperation Agreement gives birth to rights and obligations for both the Developer and the Bank, both of which have balanced positions. Additional provisions agreed upon by the Developer and the Bank are the Buyback Guarantee Agreement, which is a condition where the Developer acts as a Guarantor for the repayment of the Debtor's debt in the event of the Debtor's default in the obligation to pay installments or debts. The effectiveness of the buyback agreement can be seen from the realization data of buyback found in Developer X towards Bank A.